The Market for Policy Communication - Johan F. M. Swinnen; Thijs Vandemoortele; Mara Squicciarini (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
We develop a model of policy communication by aid agencies, NGOs and intergovernmental organizations and we show how the need for fundraising affects the policy communication strategy of these organizations. To attract more funds, organizations may bias their communication. The bias depends on the ex ante beliefs of donors and on mass media reporting.
Keywords: D83; D23; P16; L31; 330; political economy; bias; NGOs; intergovernmental organizations; fundraising; Private Entwicklungshilfe; Nichtregierungsorganisation; Kommunikation; Öffentlichkeitsarbeit; Spende; Theorie